If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b = 3x + -5 Reorder the terms: b = -5 + 3x Solving b = -5 + 3x Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Simplifying b = -5 + 3x
| 2x^2+10x-311=0 | | 8x^3-64x=0 | | 7(y-2)=1+6y | | a=2x+1 | | 7x+6x-8x-5=5 | | n/.66-11=4+n | | 140-30=p | | -6a+2a=36 | | P-1=4p+3p-13 | | 5+35x=61+55x | | t+6.5=3+-1.3 | | -12+x=x+14 | | x+12=.45x+9 | | 7x+6x-8x-5= | | 14y^2+17y-6=0 | | 12=-(x+4) | | 53+17=3276 | | 3x-2=42 | | 33=5v-2 | | 8x-3x=4x-7 | | 5+35x=55x | | 4u-6+u+3= | | 5h-4h=8 | | 8x-10x+4x= | | 3x-6+1=-2x-5-5x | | 3z+3-z=5+z+7 | | 0.666667g+6=-12 | | 100*10=m*15 | | 3x-5(x-4)=-9+3x+4 | | (y-4)-(y+6)=5y | | h=141-21t-16t^2 | | 1.2+8+x=.50x |